Výroba ocelové součásti technologií stříhání - Suchomel, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Diplomový projekt vypracovává optimální návrh technologie výroby výstřižku - součásti z ocelového plechu ČSN 11 320.3. Teoretická část popisuje problematiku technologie stříhání a na jejím základě byla navržena výroba součásti v postupovém nástroji. Ten se skládá z normalizovaných komponent a je řešen formou stojánku upnutého do výstředníkového lisu LEXN 100 C (výrobce Toma Industries), s nominální tažnou silou 1000 kN. Lis byl vybrán na základě technologických výpočtů. Práce obsahuje potřebné výpočty a výkresovou dokumentaci střižného nástroje pro výrobu výstřižku. V závěrečné části je provedeno technicko-ekonomické zhodnocení nově navržené technologie.

The master’s thesis elaborates an optimum proposal of the production technology of a cutting – a part made of steel plate 11 320.3. The theoretical part represents the problematic issue of cutting technology and on the basis of this part was designed a production of components in processual tool. The processual tool is composed of normalized components and is resolved by using a easel, which is attached into the eccentric press LEXN 100 C (producer Toma Industries) with the nominal drawing force of 1000 kN. The press was chosen on the basis of technological calculations. The work contains necessary calculations, economical evaluation and design documentation of the cutting tool for the components production. The last part contains the technical and economic evaluation of the recently designed technology.
The manufacturing of sheet metal part by blanking technology
Keywords: plošné tváření; postupové stříhání; střižný nástroj; nástřihový plán; výstřižek; surface forming; follow cutting; cutting tool; cutting plan; a cutting